PENGARUH ANALISIS FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY: PENGARUH ANALISIS FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY - Munawarah, Munawarah (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
The aim of this study is to examine and analyze Fundamental Analysis measured by Financial Ratios such as Debt to Equity Ratio (DER),Earning Per Share (EPS), Economic Value Added (EVA), and Market Value Added (MVA) to the Share Price of the Property and Real Estate sub sectors listed on the Indonesian Stock Exchange in the period 2011-2015. The research was causal research method and used secondary data. The population was 47 companies, and 12 of them were used as the samples, which taken by purposive sampling technique. The data were analyzed by using multiple linear regression analysis. The result of the research showed that simultaneously Debt to Equity Ratio (DER),Earning Per Share (EPS), Economic Value Added (EVA), and Market Value Added (MVA) had positif significant effect to Share Price. Partially, Only Economic Value Added (EVA) had no significant effect to Share Price. Debt to Equity Ratio (DER) had negatif significant effect to Share Price. While Earning Per Share (EPS),and Market Value Added (MVA) had a positif significant effect to Share Price. The R2 was 0,713, which means that 71,3 % variation of Share Price variable can be explained by variations of Debt to Equity Ratio (DER),Earning Per Share (EPS), Economic Value Added (EVA), and Market Value Added (MVA). While the remaining 28,7 % was affected by other factors.Keyword : Debt to Equity Ratio (DER),Earning Per Share (EPS), Economic Value Added (EVA), Market Value Added (MVA), and Share Price